Knowledge, Practices, and Attitudes of Nurses Regarding Non-Pharmacological Pain Management in the Midwifery Ward - Shahla Shkak Shareef; Tiran Jamil Piro (Hawler Medical University, 2023)
Background and Objectives: Pregnant women are frequently worried about labor pain, and it is usually the most important problem for them and their relatives. Non-pharmacological pain relief methods provide several benefits, such as no harmful effects on the fetus or baby, no interruption of labor, and even being pleasurable for the mother and fetus. The aim of this study was to assess the nurse's knowledge, practice, and attitude toward non-pharmacological pain management methods in the delivery room in Erbil Governorate. Method: The descriptive cross-sectional design was utilized to determine nurses' knowledge, practices, and attitudes about labor pain and non-pharmacological pain management, as well as to monitor nurses' practices in the delivery rooms during labor and delivery. A total of 78 nurses from public and private hospitals in Erbil Governorate participated in the study. Structured questionnaires and an observational checklist were used to collect data and used SPSS version 26 was used to analyze it. Result: Nurse's knowledge (N=27, 50.0%), (N=9, 37.5%) in public and private hospitals was at a good level, and they had a positive attitude (N=32, 59.3%) in public hospitals and a positive attitude (N=14, 58.3%) in private hospitals. But had a fair practice (N=19, 35.18%) in public hospitals and good practice (N=10, 41.7%) in private hospitals towards labor pain and non-pharmacological pain management. This is due to the lack of time, inadequate staff and the great workload of the staff. Conclusion: This survey showed that the knowledge of most of the nurses was at a good level, but it was weak in items such as (cold therapy, acupuncture and acupressure technique), as well as majority of them do the following practices: relaxation technique, give psychological support and, ensure that women's relatives are there during the entire labor process; and they do not use other types of non-Pharmacological